The (Im)possibility of Women's Bildungsroman - Gjurgjan, Ljiljana Ina (Array, 2012)
The article starts with contention that women's Bildungsroman can exist as such only tentatively since the ideology underwriting the genre of Bildungsroman is that of becoming a man in society. The article claims that for that reason even in Virginia Woolf's To the Lighthouse it is the main charcter (James) who reaches maturity whereas Lily Briscoe's attempt at reaching her artistic self-realization is ambivalent. The ambivalence in the theological structure of Bildungsroman is also characteristic of the novels discussed further in the essay, Sylvia Plath's The Bell Jar and Djiin in the Nightingale's Eye. Female’s subversiveness is however achieved through the re-evaluation of language in Adrienne Rich’s and A. S.Byatt’s writing. However, this attempt at re-evaluating female position is underminded but the stereotypes constantly perpetuated through popular fiction and films, such as Bridget Jones’s Diary and Devil Wears Prada.